Interpersonal Emotion Regulation in Betrayal Trauma Survivors: A Preliminary Qualitative Exploration. Issue 4 (3rd April 2023) - Kline, Nora K.; Prichett, Brianna; McKim, Katherine G.; Palm Reed, Kathleen
ABSTRACT: Interpersonal trauma, or trauma involving maltreatment by someone that a survivor has a close, personal relationship with (i.e., betrayal trauma), may be particularly predictive of alterations in interpersonal and emotion regulation processes. Social support may facilitate interpersonal emotion regulation (IER) and posttraumatic functioning, though this process may be particularly difficult for survivors of betrayal trauma. The current study includes a sample of female-identifying betrayal trauma survivors with clinically significant PTSD symptomology (N = 70). Thematic analysis was utilized to investigate how these survivors describe their affective experience and the factors that impact their willingness and comfort to engage with others during times of distress. Most participants were able to describe their emotional experiences, but provided brief, simplistic descriptions. Generally, participants reported feeling wary of sharing negative emotions with others due to fear of judgment or being seen as a burden. Findings allow us to better understand how survivors make sense of and differentiate their emotions, and their experienced benefits of or barriers to IER.